The Effect of Balimo (Zanthoxylum nitidum) Immersion Water On The Hematological Profile of White Rats (Rattus norvegicus) That Given Liquor (Ciu) - Wijaya, Panca Buana; Saraswati, Tyas Rini; Tana, Silvana; Sunarno, Sunarno; Prihastanti, Erma (Biology, Medicine, & Natural Product Chemistry, 2021)
Consumption of liquor such as Ciu in excessive doses can cause a decrease in hematological status. Balimo stem is an alternative treatment to improve hematological status due to excessive alcohol consumption because it contains alkaloids, flavonoids, and other secondary metabolic compounds, that have functions as antioxidant effects. This study aims to examine and analyze the effect of Balimo immersion water on the hematological status of mice with the observed variables, namely the erythrocytes count, hemoglobin levels, hematocrit value, and total count of leukocytes in rats that had been given Ciu. The study used 20 Rattus norvegicus male rats which were divided into 4 groups. The data were analyzed using one-way ANOVA. The results showed no significant differences (p <0.05) on the Balimo immersion water treatment, but if it was seen from the difference in the mean data of each variable, it could still be seen the difference from each treatment. In this study, it can be concluded that Balimo immersion water was able to improve the hematological status of rats that had been given Ciu liquor with a 0,2 mL dose.